Effect of betaine on muscle, liver and serum amino acid composition in finishing swine - FENG Jie; XU Zi-rong (浙江大学学报. 农业与生命科学版, 2001)
One hundred fifty finishing pigs (Duroc× Landrace×yorkshire) were allotted to five groups which received the same basal diet, supplemented with 0, 1 000, 1 250, 1 500, 1 750 mg/kg betaine. On finishing40 days feeding experiment, 60 pigs were slaughted, the longissimus dorsi, liver and serum samples were collected and amino acid composition were analysed. The results indicated that different level betaine hereof did not affect the amino acid composition of longissimus dorsi and liver, but some of the free amino acid contents were improved in serum especially the serine and valine which were increased by 14.28%(P<0.05) and 31.75%(P<0.05), respectively.